Status and Conservation Management Strategies for Threatened Plants of Jammu and Kashmir - Pant, Shreekar Pant*; Virbala Sharma (Journal of Phytology, 2011)
The state of Jammu and Kashmir harbours a rich diversity of economically important plants. A perusal of literature indicates that study pertaining to the diversity, nativity, endemism, rarity, review of in-situ & ex-situ conservation programmes, agrotechniques, medicinal plants in pharmaceutical preparations, trade and problems related to cultivation of threatened plants for conservation and strategy action plan had not been carried out so far. Therefore, in present an attempt has been made to describe 63 species (trees: 07 spp.; shrubs: 09 spp.; herbs: 47 spp.) of threatened plants. Liliaceae, Asteraceae, Apiaceae, Ranunculaceae, Ericaceae, Solanaceae, Polygonaceae, Orchidaceae, Rutaceae, Lauraceae and Gentianaceae are the dominant families. Twenty four families are represented by single species. Different plant parts such as roots/rhizomes/tubers (38 spp.), leaves (17 spp.), whole plant (10 spp.), bark (8 spp.), fruits (5 spp.), seeds (4 spp.), flowers/resin (2 spp., each) and inflorescence/stem (1 spp., each) are used for the treatment of various ailments. Amongst the threatened plants, 49 are native to the Himalayan region, 01 endemic and 17 near endemic to Indian Himalayan Region (IHR). All the described sixty three (63) species have been categorized as Critically Endangered (11 spp.); Endangered (21 spp.); Vulnerable (26 spp.); Near Threatened (02 spp.) and Least Concern (03 spp.) as per new International Union of Conservation of nature and natural resources (IUCN) criteria. Available information on threatened plants was used either traditionally or in pharmaceutical preparation. In- situ and ex- situ conservation initiatives and agrotechniques are reviewed and highlighted the problems related to its conservation. Moreover appropriate strategy and action plan for conservation and management of threatened plants has been suggested.